Evidências da herança geotectônica pré-cambriana na geração da Bacia Potiguar: um estudo geofísico multdisciplinar - Rodrigues, Rafael Saraiva (2013)
The 3D gravity modeling of the Potiguar rift basin consisted of a digital processing of gravity and aeromagnetic data, subsidized by the results of Euler deconvolution of gravity and magnetic data and the interpretation of seismic lines and wells descriptions. The gravity database is a compilation of independent geophysical surveys conducted by several universities, research institutions and governmental agencies. The aeromagnetic data are from the Bacia Potiguar and Plataforma Continental do Nordeste projects, obtained from the Brazilian Petroleum Agency (ANP). The solutions of the Euler Deconvolution allowed the analysis of the behavior of the rift main limits. While the integrated interpretation of seismic lines provided the delimitating horizons of the sedimentary formations and the basement top. The integration of these data allowed a 3D gravity modeling of basement topography, allowing the identification of a series of internal structures of the Potiguar rift, as well intra-basement structures without the gravity effect of the rift. The proposed inversion procedure of the gravity data allowed to identify the main structural features of the Potiguar rift, elongated in the NE-SW direction, and its southern and eastern faulted edges, where the sedimentary infill reachs thicknesses up to 5500 m. The southern boundary is marked by the Apodi and Baixa Grande faults. These faults seem to be a single NW-SE oriented fault with a strong bend to NE-SW direction. In addition, the eastern boundary of the rift is conditioned by the NE-SW trending Carnaubais fault system. It was also observed NW-SE oriented faults, which acted as transfer faults to the extensional efforts during the basin formation. In the central part of the residual anomaly map without the gravity effect of the rift stands out a NW-SE trending gravity high, corresponding to the Orós-Jaguaribe belt lithotypes. We also observe a gravity maximum parallel to the Carnaubais fault system. This anomaly is aligned to the eastern limit of the rift and reflects the contact of different crustal blocks, limited by the eastern ward counterpart of the Portalegre Shear Zone